1997
DOI: 10.1021/bp970061+
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Restriction Enzyme EcoRI Dried with Trehalose and Other Selected Glass-Forming Solutes

Abstract: The stabilization of the restriction enzyme EcoRI by its incorporation into aqueous glass-forming carbohydrate or polymer solutions, followed by vacuum-drying to low moisture, has been studied. Glass-forming solutes included trehalose, sucrose, lactose, maltose, raffinose, maltodextrin DE 10, and poly(vinylpyrrolidone) (molecular weight 40,000, PVP). Among the solutes examined, trehalose and sucrose protected the enzyme most effectively during storage at 37 and 45 degrees C. The restriction enzyme dried with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Variations in chemical stability that do not seem to be related to global mobility have also been observed for various solid proteins, including restriction enzyme EcoRI dried with sucrose, trehalose, maltodextrin or PVP, 104 lactase and invertase lyophilized with trehalose, maltose, lactose, sucrose, raffinose, maltodextrin, casein or PVP, 22,[105][106][107][108] and glucose-6-phosphate dehydrogenase lyophilized with dextran, sucrose or raffinose. [109][110] It is not easy to explain the lack of correlation between chemical stability and global mobility for proteins because of many complicated factors possibly affecting the chemical stability.…”
Section: Examples For Chemical Stability Not Apparently Related To Glmentioning
confidence: 96%
“…Variations in chemical stability that do not seem to be related to global mobility have also been observed for various solid proteins, including restriction enzyme EcoRI dried with sucrose, trehalose, maltodextrin or PVP, 104 lactase and invertase lyophilized with trehalose, maltose, lactose, sucrose, raffinose, maltodextrin, casein or PVP, 22,[105][106][107][108] and glucose-6-phosphate dehydrogenase lyophilized with dextran, sucrose or raffinose. [109][110] It is not easy to explain the lack of correlation between chemical stability and global mobility for proteins because of many complicated factors possibly affecting the chemical stability.…”
Section: Examples For Chemical Stability Not Apparently Related To Glmentioning
confidence: 96%
“…During drying, a certain degree of deterioration may occur, and the stabilization of biomaterials by their incorporation into carbohydrate and/ or polymer solutions before drying is a known preservation procedure (Colaço, Sen, Thangavelu, Pinder, & Roser, 1992;Crowe, Crowe, Carpenter, & Winstrom, 1987;Leslie, Israeli, Ligthart, Crowe, & Crowe, 1995;Rossi, Buera, Moreno, & Chirife, 1997). Many sugars are involved in preservation mechanisms of living organisms under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the possible effects of the physical characteristics of the matrices discussed above (free volume and plasticization) on α-amylase stabilization, interaction between matrices and enzyme, which could result in specific protective effects, must also be considered. The saccharide raffinose protected enzymes lactase, invertase and restriction enzymes (4,18,23) at the same level as trehalose, in various conditions of temperature and water content. It has been suggested that sugars, like other polyols, are able to make multiple external hydrogen bonds that could replace the essential water molecules involved in the maintenance of the tertiary structure of proteins (1).…”
Section: Resultsmentioning
confidence: 99%